GENDER-BASED DISCRIMINATION EXPERIENCED BY THE MAIN CHARACTER IN HANDMAID'S TALE BY MARGARET ATWOOD - Birgita, Joscelin; Mau, Emanuella Christine Natalia (LINGUAMEDIA Journal, 2023)
The Handmaid Tale is a literary work created by Margaret Atwood in 1985. This novel tells of a woman named Offred who lives in a dystopian country called the Republic of Gilead. She experienced various forms of gender discrimination. This novel reflects criticism of forms of gender discrimination where women are treated inhumanely and do not have freedom in their lives. Two research questions are addressed in this study. The first question aims to find out the forms of gender discrimination experienced by Offred. The second question aims to find out how the main character deals with the gender discrimination she experiences. The research method used in this research is qualitative. Sources of this research include novels, books, and journals. Three feminist theories are used in this study to analyze and answer research questions: Rivkin and Ryan, Simone de Beauvoir, and Laura Mulvey. This research's impact is encouraging women to engage in critical thinking and not make themselves objects to men. In conducting this study, the researcher identified various forms of gender discrimination that contribute to the development of the main character. Keywords: Gender discrimination, feminism, gender roles